Financial deepening and innovation efficiency: The role of political institutions - Chun-Yu Ho; Shaoqing Huang; Hao Shi; Jun Wu (Asian Development Bank Institute (ADBI), 2017)
This study investigates the effects of financial deepening on innovation efficiency for various democratic levels of political institutions using panel data from 69 countries spanning 1970-2010. Banking market deepening is associated with increased innovation efficiency only when political institutions are sufficiently democratic. In contrast, the enhancing effect of stock market deepening on innovation efficiency requires a lower level of political democracy. Furthermore, the results are stronger for countries with lower incomes than for countries with higher incomes. Our results are robust for the use of the instrumental variable approach and alternative measures for financial deepening, democracy, and innovation inputs.
Keywords: E02; G20; O30; 330; Economics; Finance sector development